2007
DOI: 10.1534/genetics.107.075770
|View full text |Cite
|
Sign up to set email alerts
|

State IIDissociationElement Formation FollowingActivatorExcision in Maize

Abstract: Active Activator (Ac) elements undergo mutations to become nonautonomous Dissociation (Ds) elements at a low frequency. To understand the mechanism of Ds formation, we have developed high-throughput genetic and molecular screens to identify these rare Ds derivatives generated from any Ac insertion in the maize genome. Using these methods we have identified 15 new Ds elements derived from Ac insertions at eight different loci. Approximately half of the Ds elements contain filler DNA inserted at the deletion jun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 75 publications
2
18
0
Order By: Relevance
“…In the presence of Ac, chromosome-breaking Ds elements (Ds, state I) can convert to a different state (Ds, state II) that rarely causes chromosome breakage (McClintock, 1949). State II Ds elements have been cloned from a number of loci; sequence analysis revealed that many of these were internally deleted versions of Ac (Weil et al, 1992;Yan et al, 1999;Conrad et al, 2007). A smaller number of State I Ds elements have also been cloned; their structures include doubleDs (a state II Ds inserted into another copy of the same element in the opposite orientation; Doring et al, 1984;Weck et al, 1984) and sesquiDs (an internal deletion derivative of doubleDs; Martinez-Ferez and Dooner, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…In the presence of Ac, chromosome-breaking Ds elements (Ds, state I) can convert to a different state (Ds, state II) that rarely causes chromosome breakage (McClintock, 1949). State II Ds elements have been cloned from a number of loci; sequence analysis revealed that many of these were internally deleted versions of Ac (Weil et al, 1992;Yan et al, 1999;Conrad et al, 2007). A smaller number of State I Ds elements have also been cloned; their structures include doubleDs (a state II Ds inserted into another copy of the same element in the opposite orientation; Doring et al, 1984;Weck et al, 1984) and sesquiDs (an internal deletion derivative of doubleDs; Martinez-Ferez and Dooner, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…To eliminate TPase expression from ps1(Ac), a genetic scheme was used to recover five Ds derivatives from the Ac insertion at ps1(Ac) (Conrad et al 2007). Four of the five ps1(Ds) alleles were identified as internal deletion derivatives that do not produce functional TPase protein but retain the element at the original genomic location as the donor Ac.…”
Section: Resultsmentioning
confidence: 99%
“…One base pair of the target site duplication adjacent to this Ds insertion was also deleted. In addition to the 3563-bp deletion in ps1(Ds2), filler DNA was also present at the deletion junction, which originated from both Ac and ps1 59-UTR sequences that flanked the insertion site (Conrad et al 2007).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations